2007
DOI: 10.1074/jbc.m608857200
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Tyrosine Phosphorylation Enhances Paclitaxel-mediated Cytotoxicity

Abstract: Caveolin-1 (CAV1), a highly conserved membrane-associated protein, is a putative regulator of cellular transformation. CAV1 is localized in the plasmalemma, secretory vesicles, Golgi, mitochondria, and endoplasmic reticulum membrane and associates with the microtubule cytoskeleton. Taxanes such as paclitaxel (Taxol) are potent anti-tumor agents that repress the dynamic instability of microtubules and arrest cells in the G 2 /M phase. Src phosphorylation of Tyr-14 on CAV1 regulates its cellular localization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…The association of the microtubule-associated protein with microtubules in tumor cells may affect the sensitivity of cancer cells to paclitaxel-induced apoptosis. Caveolin-1 has been reported to be associated with microtubules and to enhance paclitaxel-mediated apoptosis of MCF-7 cells (29). Low expression of the microtubule-binding protein, tau, was reported to enhance the sensitivity of human breast cancer to http://bmbreports.org paclitaxel treatment (30).…”
Section: Discussionmentioning
confidence: 99%
“…The association of the microtubule-associated protein with microtubules in tumor cells may affect the sensitivity of cancer cells to paclitaxel-induced apoptosis. Caveolin-1 has been reported to be associated with microtubules and to enhance paclitaxel-mediated apoptosis of MCF-7 cells (29). Low expression of the microtubule-binding protein, tau, was reported to enhance the sensitivity of human breast cancer to http://bmbreports.org paclitaxel treatment (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1, as the principal component of caveolae, plays an important role in material transportation, endothelial infiltration and tumorigenesis (18). Cav-1 acts as a scaffolding protein by interacting with signaling molecules through a caveolin scaffolding domain to modulate gene expression, signal transduction and protein translocation in the cell membrane (18 invasion and metastasis (19)(20)(21)(22). Additionally, it has been shown that Cav-1 is closely associated with the development of drug resistance (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Caveolin-1 (Cav-1) is a structural protein of 50 to 100 nm present in invaginations of the cell membrane (caveolae) (Bat'ová et al, 2003;Williams and Lisanti, 2005;Sotgia et al, 2006;Williams et al, 2006;Shajahan et al, 2007). Caveolae are enriched by sphingolipids and cholesterol (Zhu et al, 2008) and are directly involved in vesicular trafficking and signal transduction (Bouras et al, 2004;Chen et al, 2004;Elsheikh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%